Hankinson’s formula evaluation as a resistance estimator for the bonded joints under compressions and for mechanic development in bonded joints under torsion (Research, Society and Development, 2022)
Hankinson’s formula estimates strength properties of wood when the material is receiving forces inclined in relation to the fiber direction. In Brazil, by force of normative orientation, a fixed value equal to 2 is usually used for the exponent β of the sine and cosine of the formula, but better adjustments can occur for exponents different from this value. The objective of this work was to evidence, from five independent experiments, the adequacy of Hankinson’s formula to estimate the strength of glued joints at different angles, when ruptured under compression. Additionally, it was sought to analyze the difference in mechanical performance of glued joints when the test is done by compression or by torsion. In this work, the values of parameters β varied between 1.82 and 2.18, with an average of 2.02, which is close to the value adopted in the standard. The bonded joints ruptured by compression presented loss of strength with the increase of the bonding angle. In the torsion test, the resistance suffered little influence of the glueing angle. It was verified that Hankinson’s formula is adequate to estimate the strength of glued joints at different angles between wood fibers, when the rupture occurs by compression, but it does not seem adequate to obtain an estimate of strength under torsion. Glued joints broken under compression showed different strength than glued joints broken under torsion. Overall, both Hankinson’s formula and tests conducted under torsion may allow the verification of glued joints subjected simultaneously to forces and moments.